O emblema da razão : movimento operário e historiografia - Maquera, Angelita Cristina (2016)
During the 1980s, it has proliferated in Brazil works on the history of the Brazilian working class of the early twentieth century. This study aims to present the main characteristics of these studies, particularly highlighting their theoretical and methodological aspects. In addition to understand the emergence of social movements from 1978, the incentive to perform such studies relate to legitimate issues linked to the historical, social and political context experienced by the Brazilian society of the twentieth century. Thus, to analyze the main aspects of such works, it is noted that most of them emphasized the period known as the First Republic, especially the manifestations that occurred between the years 1917 to 1921. Some works have escaped that delimitation and presented modes of working resistance in the 1930s and 1940s, as there were also concerns about the present itself, primordially, on the new forms of working organization that materialized in 1978. It is understood that the changes occurred in Brazilian society of those years, together with the renovations occurred in the field of history, allowed a singular historiography production, that breaking with the analysis models, even before consolidated, made emerge the working class as the subject of its own history